2019
DOI: 10.1097/eja.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of ultrasound-guided interscalene block vs. supraclavicular block for ambulatory arthroscopic rotator cuff repair

Abstract: BACKGROUNDUltrasound-guided interscalene block (ISB) is the reference technique for pain control after ambulatory upper limb surgery, but supraclavicular block (SCB) is an alternative.OBJECTIVESThe aim of this study was to compare the efficacy of SCB vs. ISB in patients undergoing ambulatory arthroscopic rotator cuff repair (ARCR), with the hypothesis of noninferiority of SCB analgesia compared with ISB.DESIGNA randomised, single-blind, noninferiority study.SETTINGHôpital Privé Jean Mermoz, Centre Paul Santy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
(42 reference statements)
0
16
0
2
Order By: Relevance
“…By the final follow-up, 212 patients were lost. A total of 74 of the 79 studies were single-centered [ 1 , 2 , 5 , 6 , 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , ...…”
Section: Resultsmentioning
confidence: 99%
“…By the final follow-up, 212 patients were lost. A total of 74 of the 79 studies were single-centered [ 1 , 2 , 5 , 6 , 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , ...…”
Section: Resultsmentioning
confidence: 99%
“…3 At the same time, considering the recent socioeconomic issues that there were a lot of trials to reduce hospitalization days and minimize opioid consumptions, regional block combined with general anesthesia was widely performed. 5,7 Also, there were reports that for reducing rebound pain, continuous nerve block using indwelling catheter was more effective than single. 8,9 Although ISB catheterization is one of the most effective methods, it can cause complications such as phrenic nerve palsy/pneumothorax and temporal brachial partial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Among them, nerve block for postoperative pain control, which includes interscalene block, supraclavicular block, and suprascapular nerve block, has been used extensively to reduce pain and side effects of medications. [4][5][6][7] In recent years, several studies have reported that continuous interscalene block (ISB) is effective in controlling postoperative pain and decreasing rebound pain. [8][9][10] ISB targets the C5 and C6 nerve roots of the brachial plexus, where the suprascapular nerve and axillary nerve innervate the shoulder joint.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies evaluated nerve blocks for rotator cuff repair specifically. 32,37,44,87 Cabaton et al 37 found that a supraclavicular nerve block with 100 mg levobupivacaine and clonidine provided similar pain management but much less opioid consumption from 0 to 48 hours postoperatively compared to an ultrasound-guided interscalene nerve block with the same dosages. Wong et al 87 shows that an interscalene block with 20 mL of .2% ropivacaine decreases opioid consumption at 72 hours postoperatively compared to the same block with only .1% ropivacaine.…”
Section: Rotator Cuff Repairmentioning
confidence: 99%